Ureteral injury following vertebral body tethering for adolescent idiopathic scoliosis - JuliAnne R. Rathbun; Daniel S. Hoernschemeyer; Mark R. Wakefield; Elizabeth A. Malm-Buatsi; Katie S. Murray; Venkataraman Ramachandran (Elsevier, 2019)
Adolescent idiopathic scoliosis (AIS) is a deformity of the spine of unknown etiology and no definitive cure. A novel technique for correction during growth known as vertebral body tethering (VBT) was introduced in 2005 in animal models, and then quickly adapted for human implementation [Courvoisier, 2015]. This method is in the early stages of growth and adaptation as well as evaluating risks to improve safety and feasibility. Some of the most common complications reported are atelectasis [Newton, 2018], proximal junctional kyphosis and reoperation for device breakage or addition [Hardesty, 2017]. There are no case reports describing ureteral injury following VBT. We present a case of primary ureteral injury following VBT with subsequent erosion and stricture formation requiring definitive ureteral reconstruction. We discuss the possible causes of this complication, its management, follow up, and short-term outcome. Keywords: Vertebral body tethering, Surgical complication, Ureteral injury